The role of agencies in creating network approach in higher education - Dujmović, Jelena (Array, 2021)
An analysis of different aspects regarding the creation of networks within the Croatian higher education system is presented in the paper. The larger part of the paper refers to the analysis of public services in general and the network approach in public administration in particular. The state of the higher education system is presented through the inclusion of market and network principles and the establishment of numerous actors in this field by which effectiveness of this field of public administration is trying to be improved. The aim of the detailed examinations is to pro-vide an overview of all relevant actors whose interactions and roles resemble network-like relationships. To examine the starting hypothesis that neo-managerial approach leads to networking within the higher education system, an empirical study was conducted at the Josip Juraj Strossmayer University in Osijek, Croatia among the teaching staff and students. The final chapters of the paper present and discuss research results which principally support the initial assumptions.